1985
DOI: 10.1063/1.334816
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric response function for a quasi-one-dimensional semiconducting system

Abstract: We have obtain~ t~e ~ielectric response function for a quasi-one-dimensional electron gas (Q 1 D). In .the statIC hIDlt (llJ = 0), we find that the dielectric function has a logarithmic singularity ~ a fun~tlon of wave vector when q = 2k f when the electron gas is degenerate, but that this sm~anty no lo~ge~ ~urs when the electron gas is nondegenerate. This singularity is ~nsld~red to be mdlcatlve of the Peierls transition which has been predicted to occur in a one-dImenSIOnal electron gas. As the radius of our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(30 citation statements)
references
References 13 publications
1
29
0
Order By: Relevance
“…͑27͒ at k ϭ2k F is divergent and is to be replaced [2][3][4] with the one at a low temperature (k B TӶE F ):…”
Section: B Density Of Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…͑27͒ at k ϭ2k F is divergent and is to be replaced [2][3][4] with the one at a low temperature (k B TӶE F ):…”
Section: B Density Of Statesmentioning
confidence: 99%
“…The quasi-one-dimensional electron gas ͑1DEG͒ in the wire is generally violently affected by disorder arising from impurity doping. The disorder has been shown to lead to remarkable changes in the observable properties of the wire, e.g., the electron mobility [1][2][3][4][5] and the density of states ͑DOS͒. [6][7][8][9] It should be mentioned that all existing theories 1-9 of the disorder effect from impurity doping in QWR's were established by assuming that the ionized impurities are absolutely randomly distributed in the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Much work has been devoted to the study of hydrogenic impurity states in these systems [6 -33]. Binding energy calculations for hydrogenic impurities in quantum wells (QWs) [6 -8], quantum well wires (QWWs) [9][10][11][12][13][14][15][16][17][18][19][20][21] and quantum dots (QDs) [22][23][24] have been performed. It is found that when the dimensions of the system are reduced, the quantum size becomes clear and the effective strength of the coulomb interaction increases.…”
Section: Introductionmentioning
confidence: 99%
“…The bare potential in NWs is screened due to the presence of free carriers. The quasi 1D screening function (q, 0) can be calculated using the self-consistent procedure outlined by Lee and Spector [11]; we have included the effect of the dielectric mismatch to their screening theory. At low temperatures, the carriers contributing to transport are predominantly those at the Fermi level, and the momentum change upon scattering is q ≈ 2k F , where k F is the Fermi wavevector.…”
Section: Arxiv:09062371v1 [Cond-matmes-hall] 12 Jun 2009mentioning
confidence: 99%